2018
DOI: 10.1051/e3sconf/20183111004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work-Family Supportive Supervisors on Job Involvement and Job Satisfaction with Career Competencies as an Intervening Variable

Abstract: This study was conducted to explore the relationship between work-family supportive supervisor, career competencies, job involvement, and job satisfaction. Data were collected from a sample of 162 respondents who worked as a nurse at hospital in Jakarta, Indonesia. This study used Structural Equation Modeling (SEM) to examine and estimate the relationship between the constructs. The study results indicate that work-family supportive supervisor has a positive and significant impact on career competencies, caree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…A study by Park (2020aPark ( , 2020b demonstrated that the knowingwhy of human resource practitioners includes identity, credibility and career clarity. The development of the knowing-why career competency is also influenced by career values, meanings, interests and motivations (Dickmann and Harris, 2005;Sturges et al, 2003). Another study categorized gig workers' competencies, precariousness and motivation to engage, navigate and understand their roles as knowing-why (Duggan et al, 2021).…”
Section: Career Competency Subconstructions and The Intelligent Caree...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Park (2020aPark ( , 2020b demonstrated that the knowingwhy of human resource practitioners includes identity, credibility and career clarity. The development of the knowing-why career competency is also influenced by career values, meanings, interests and motivations (Dickmann and Harris, 2005;Sturges et al, 2003). Another study categorized gig workers' competencies, precariousness and motivation to engage, navigate and understand their roles as knowing-why (Duggan et al, 2021).…”
Section: Career Competency Subconstructions and The Intelligent Caree...mentioning
confidence: 99%
“…4.2.2 Knowing-how. According to the concept of knowing-how, individuals find and promote job redesigns that accommodate their distinct talents and potential while extending beyond their current knowledge, skills and abilities (Defillippi and Arthur, 1994;Sturges et al, 2003). Knowing-how competencies reflect career-related skills and job-related knowledge (Francis-Smythe et al, 2013).…”
Section: Career Competency Subconstructions and The Intelligent Caree...mentioning
confidence: 99%
“…Anggota keluarga dianggap sebagai komponen penting dari pengaturan keluarga. Anggota keluarga menganggap keluarga sebagai kelompok penolong yang selalu siap memberikan dukungan dan bantuan bila diperlukan, (Suharnomo & Johnpray, 2018). Menurut Friedman (dalam Yulianto, 2018) bahwa bentuk dukungan keluarga terdiri dari: dukungan informasional, dukungan instrument, dukungan penilaian, dan dukungan emosi.…”
Section: Landasan Teori 21 Dukungan Keluarga Dukungan Organisasi Buda...unclassified
“…As the main resource for the company, employees are currently experiencing many changes in terms of demographics, including an increase in working women or individuals who carry out multiple roles in their lives (Crain & Stevens, 2018). In carrying out these various roles, leaders are needed who can understand or can informally assist employees so that all roles can be carried out properly, also known as family-supportive supervisor behaviours (Suharnomo & Johnpray, 2018;Han & McLean, 2020;Shi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%